Meteorological Impacts of Sea Surface TemperatureVariations Along Coastline of Karachi - Shahnam Ali; Ramzan Hassan; Muhammad Fawad Ul Karim (Spectrum of Engineering Sciences, 2025)
Variability of sea surface temperature (SST) is important as theduration and intensity of SST provide the basis for studies relatedto climatic change scenario. In the present study, monthly datasetsof Sea Surface Temperature (SST) relation to WindSpeed, Temperature and Sea Level Pressure (SLP) for the periodof sixyears are used for the period 2004-2009. The SST data is obtainedfrom Moderate Resolution Imaging Spectroradiometer (MODIS). We selected an area for latitude (24°-25° N) and longitude(66.6°-67.5° E) as a reference point to show the variations of SSTalongcoastline of Karachi located in north Arabian sea and its relationtometeorological parameters Wind Speed, Temperature, SLP. Meteorological parameters datasets are obtained fromweatherUnderground Karachi Airport Station. The trend analysis of monthly mean SST shows that SST variations dominated insummerespecially in the month of June in. SST is related to WindSpeed, there is positive correlation between SST and windspeed. Generally wind Speed is higher in summer and lower inwinteralong the coastline of Karachi. SST and air Temperature has shownpositive correlation over the coastline of Karachi. The correlationbetween SST and Sea level pressure negative in the studyarea.Meteorological impacts results heavy precipitation, tropical cyclone, sea level rise and flood in coastline of Karachi. Keywords: SST, Wind Speed, Air Temperature, MODIS (ModerateResolution Imaging Spectroradiometer), tropical cyclone, heavyprecipitation.